Analisis Hubungan Skill dan Motivasi dengan Penginputan Data Istitha‘Ah Jemaah Haji Wilayah Kerja Dinas Kesehatan Provinsi Sumatera Barat - Alfita Dewi; Annisa Novita Sary; Eliza Trisna Dewi; Putri Ismalya Yulinda (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
According to the presentation coverage report, the number of Hajj pilgrims' health data on SISKOHATKES within 2 (two) weeks of departure must be 100% input. However, there has been a decrease in the percentage of target achievement in inputting SISKOHATKES data for 5 years until 2022 (96.98%). This research aims to determine the factors related to inputting health istitha'ah data for Hajj pilgrims by the management of the integrated Hajj computerized health system in the work area of the West Sumatra Provincial Health Service in 2023. This research is a type of observational research with a cross-sectional approach. The research was conducted at the West Sumatra Provincial Health Service from May to August 2023. The sample for this research was all 48 Siskohatkes managers. Data was obtained through a Google Form survey. The analysis uses the Chi-square test, namely connecting two variables, the independent variable and the dependent variable. The significance level is 95% (α= 0.05). Based on the research results, it is known that (P-value = 0.008) there is a relationship between Ability (Skill) and the Performance of SISKOHATKES Managers, (P-value= 0.001) there is a relationship between Work Motivation and Performance of SISKOHATKES Managers. The conclusion of this research is that there is a relationship between skills, work motivation and training and employee performance in the work area of the West Sumatra Provincial Health Service. It is hoped that organizations in improving employee performance will focus more on motivation, training and improving their abilities to achieve performance goals.